Enhanced visible-light induced degradation of benzene on Mg-ferrite/hematite/PANI nanospheres: In situ FTIR investigation - Shen, Y.; Zhao, Q.; Li, Xin Yong; Yuan, D.; Hou, Y.; Liu, Shaomin (Elsevier BV, 2012)
The dramatic enhanced visible-light photocatalytic activity of Mg-ferrite/hematite nanospheres photocatalysts on benzene were obtained after hybridized by polyaniline (PANI) using the chemisorption method. The samples were characterized by scanning electron microscope, transmission electron microscopy, X-ray diffraction, Fourier transform infrared spectra and UV–Vis diffuse reflectance spectroscopy. The enhancement of photocatalytic degradation of benzene under visible-light irradiation was mainly ascribed to the high efficiency of charge separation induced by the hybrid effect of PANI and Mgferrite/hematite. By using the in situ FTIR technique, ethyl acetate, carboxylic acid and aldehyde could be regarded as the intermediate products, and CO2 is determined as the final product during the reaction process.